Poor, Hungry and Ignorant: Numeracy and the Impact of High Food Prices in Industrializing Britain, 1780-1850 - Jörg Baten; Dorothee Crayen; Joachim Voth (Verein für Socialpolitik, 2010)
This paper uses the ability to recall one's age correctly as an indicator of numeracy. We show that low levels of nutrition impaired numeracy in industrializing England, 1780-1850. Numeracy declined markedly among those born during the war years, especially where wheat was dear. England's nascent welfare state mitigated the negative effect of high food prices on cognitive skills. Nutrition during early development mattered for labor market outcomes: individuals born in periods or countries with high age heaping were more likely to sort into occupations with limited intellectual requirements.
Keywords: O11; O15; N33; 330; nutrition; cognitive development; age heaping; numeracy; occupational choice; Industrial Revolution; social spending; poverty traps; effects of war